Resistance, Protest, and Knowledge: Indigenous Appropriation of Medievalism in Ibero- and Latin America - Beck, Lauren (Revista Canadiense de Estudios Hispánicos, 2021)
Scholars have yet to consider how medievalism offers a potent retreat from the settler-colonial project precisely because the Indigenous Middle Ages excluded Europe, and vice versa, through the mechanism of nonmodernity. By considering how modern Indigenous authors and artists reach to medieval-nonmodern Indigenous and European forms of expression in Ibero-America and Latin America, we theorize how medievalism was and remains a significant tool of resistance throughout the colonial and settler-colonial periods. This approach will allow us to find ways of undermining the modern-colonial matrix of power’s temporality at its intersection with decoloniality.